Evaluating Surface Water Quality Using Indexes of Water Quality and Plankton Diversity - Thanh Giao Nguyen; Nhien Thi Hong Huynh (Civil Engineering Journal, 2023)
The study aimed to assess the relationship between surface water quality and the diversity of planktonic communities in An Giang province, Vietnam. The national technical regulations on surface water quality, the water quality index (WQI), and the Shannon-Wiener diversity index (H') were applied to evaluate water quality. The considerable influence of water quality parameters on the dominant plankton was determined by canonical correspondence analysis (CCA) and similarity percentage analysis (SIMPER). The results showed that water quality was contaminated by organic matter, total suspended solids (TSS), and microorganisms. WQI values classified water quality as ranging from bad to good. The species composition of phytoplankton was dominated by two phyla, Chlorophyta and Bacillariophyta, and that of zooplankton was the Rotifera group. SIMPER analysis identified phytoplankton species with dominant density, including Melosira granulata, Pediastrum duplex, Anabaena sp., and Lyngbya circumcreta. Microcyclops varicans, Filinia longiseta, Trichocerca pusilla, Copepoda nauplius, Brachionus caudatus, and Polyarthra vulgarisdominated the density of zooplankton. Temperature, pH, TSS, ammonium, orthophosphate, and coliform considerably influence the dominant species composition of plankton. However, the indicators of diversity and composition of plankton were unable to completely reflect water quality. These findings could contribute to the indicator selection in developing the monitoring water quality programs. Doi: 10.28991/CEJ-2023-09-05-011 Full Text: PDF